POSITIF BEHAVIOR AND ACHIEVEMENTS IN BROKEN HOME - Nyi Anisah; Siti Nursanti; Muhammad Ramdhani (Universitas Djuanda Bogor, 2021)
Divorce is an event that causes separation between father, mother and child which occurs due to various factors. Separation will bring a problem, one of which is on the development of a child. The purpose of this study was to determine what factors support broken home children being able to show positive behavior and have achievements. The method in this research is qualitative with a case study approach with a multi-case design, data collection techniques by interview and literature study. The results showed the role of interpersonal communication that goes well between parents and children can have a positive impact on children's development. In addition, the role of family communication is also very important for children's behavior and achievement. Good family communication can determine a child's behavior, how the family communicates and how to educate children will affect a child. In addition to the role of interpersonal and family communication, there are interpersonal communication factors that can influence such as openness, trust, empathy and supportive attitudes. The conclusion of this study is that good interpersonal communication and family communication can be a measure of the character development of broken home children and there are other supporting factors that can influence the success of good behavior and achievement of a broken home child.